Late effects care for childhood brain Tumor Survivors: A Quality-Improvement Initiative. (6th May 2022) - Cacciotti, Chantel; Fleming, Adam; Duckworth, JoAnn; Tseitlin, Hanna; Anderson, Loretta; Marjerrison, Stacey
Abstract: Childhood and adolescent brain tumor survivors are at risk for long-term consequences of therapy. We reviewed adherence to long-term follow-up (LTFU) guidelines, assessed provider perspectives, and studied the needs, experience and quality of life (QOL) of pediatric malignant brain tumor survivors in the McMaster Children's Hospital Neuro-Oncology clinic. LTFU areas for improvement were evaluated using an anonymous health provider needs assessment questionnaire. The Cancer Care Experience Questionnaire (CCEQ), Cancer Worry Scale (CWS), Self-Management Skills Scale (SMSS), and PedsQL measured parents/patients' needs and QOL. Individual care plans were based on the Children's Oncology Group (COG) LTFU guidelines. Based on 17 responses, staff perceived areas for improvement included: increased multi-disciplinary participation, improved patient education and increased surveillance for therapy-related late effects. Thirty-two families participated, most felt they received high-quality care. Mean cancer worry scores were low (71.8 (± 28.4)). Survivors reported limited self-management skills (58.5 (±18.2)), requiring support with medical needs and activities of daily living. Overall median QOL scores were 'good' (parental report 72.3 (±17.7), survivor 68.2 (±16.6)). Utilizing survivorship guidelines and assessments from patients, caregivers and health providers, we implemented improvements in our provision of neuro-oncology survivorship care. Lessons learned may assist other LTFU programs.